ANALISIS KETERSEDIAAN AIR DI KAWASAN RAWA TANJUNG SENAI KABUPATEN OGAN ILIR - Ferdy Fajar Riansyah; Achmad Syarifudin; Henggar Risa D (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Water availability in swamp areas plays a crucial role in supporting community life and socio-economic activities. This study aims to analyze water availability in the Tanjung Senai swamp area, Ogan Ilir Regency. This area has extensive swampland potential, but frequently experiences fluctuations in water availability due to climate change and suboptimal water resource management. The data used in this study are secondary and primary, consisting of maximum annual rainfall data from 2012 to 2023, obtained from the Indralaya Rainfall Station. The methods used include frequency analysis, probability distributions (Normal, Log Normal, Log Pearson Type III, Gumbel), and data goodness-of-fit tests using the Kolmogorov-Smirnov and Chi-Square tests. The analysis results indicate that the Normal distribution best describes the rainfall characteristics in the area. Using the design discharge from the rational method and rainfall intensity from the Normal distribution, the annual water availability volume is 172.8 million m³. These results are expected to serve as a reference for sustainable water resource management and planning in the Tanjung Senai swamp area.Keywords: Water availability, Rainfall, Lowland swamp, frequency distribution